Bed load transport in managed steep-gradient headwater streams of southeastern Alaska - Gomi, Takashi; Sidle, Roy C. (Water resources research, 2003)
Bed load transport was investigated in four headwater streams in southeastern Alaska subjected to different management and disturbance regimes. Bed load yield was positively correlated to peak discharge during the fall 1999 monitoring period. Fine bed load materials (1–11 mm) that were supplied from hillslope sources were equally mobilized during most storm events. Medium‐sized bed materials (11–200 m) were only partially mobilized even during large storms, whereas large particles (>200 mm) were immobile and often formed interlocking channel structures. The transport distances of medium‐size materials depended on amount of channel obstructions (e.g., woody debris) and sediment supply conditions; both of these factors were influenced by the occurrence of mass movement, timber harvesting, and the related recovery processes. The highest total bed load yield was observed in a channel affected by a debris flow in 1993. Total sediment yields are similar among channels with old‐growth, clear cut (logged 4 years before monitoring), and young alder (affected by landslides and debris flows in 1961) riparian stands. By comparing the old‐growth and young alder channels, it appears that bed load yield recovers from debris flow disturbances in about 40 years; however, recovery of channel conditions (e.g., reach types and woody debris) may take much longer. Effects of timber harvesting on bed load transport are controlled by sediment linkages between hillslopes and channels related to the occurrence of mass movement.